ANALYSIS OF CONSUMER PROTECTION OVER CELEBRITY ENDORSEMENT PRODUCT INFORMATION THROUGH INSTAGRAM MEDIA - Putri, Andi Istiana Inayah Dwi; Rahman, Ali (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
This study aiming For analyze pattern connection law between the parties namely perpetrator business, party consumers, and influencers who advertise and to analyze protection law consumer to product dangerous promoted? celebrity through endorsements on Instagram. The method used in study that is method law normative. In research this , material the law used differentiated into two, namely primary and secondary. The results of the research show that activities carried out between perpetrator business, celebrity, and consumer cause existence connection law Agreement Work as regulated in 1601a of the Civil Code. The perpetrator business and consumers have connection law, namely agreement sell purchase as regulated in Article 1457 of the Civil Code. Celebgrams and consumers No own connection law Because anything, except celebrity known by the public consumers and idolized, so that consumer will interested use product anything used by celebrities, including? cosmetics and protection law to consumer namely demand change loss, for party consumers (followers) who experience loss consequence existence a activity endorsement entitled For get protection in accordance with what is written in UUPK.